2020
DOI: 10.3390/ijms21207471
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Microbiota and Brain Health: Unraveling the Network Intersecting Metabolism and Neurodegeneration

Abstract: Increasing evidence gives support for the idea that extra-neuronal factors may affect brain physiology and its predisposition to neurodegenerative diseases. Epidemiological and experimental studies show that nutrition and metabolic disorders such as obesity and type 2 diabetes increase the risk of Alzheimer’s and Parkinson’s diseases after midlife, while the relationship with amyotrophic lateral sclerosis is uncertain, but suggests a protective effect of features of metabolic syndrome. The microbiota has recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 389 publications
(423 reference statements)
0
41
0
2
Order By: Relevance
“…The approach of this therapy is to not specifically target microbial composition in the gut but rather administer or inhibit metabolites in order to counteract the negative side effects of microbiome disruptions [ 113 ]. In addition, some studies have implicated the importance of dietary choices and exercise in improving microbiome health and neuronal health [ 114 , 115 ]. For example, alpha linoleic acid (ALA) an omega-3 polyunsaturated acid isolated from plant sources such as walnuts and soybean oil has been well documented in its role in brain development, anti-inflammatory, and antioxidative activities particularly in Alzheimer’s models [ 116 , 117 ].…”
Section: Therapeutic Strategies For Chemotherapy-induced Inflammatmentioning
confidence: 99%
“…The approach of this therapy is to not specifically target microbial composition in the gut but rather administer or inhibit metabolites in order to counteract the negative side effects of microbiome disruptions [ 113 ]. In addition, some studies have implicated the importance of dietary choices and exercise in improving microbiome health and neuronal health [ 114 , 115 ]. For example, alpha linoleic acid (ALA) an omega-3 polyunsaturated acid isolated from plant sources such as walnuts and soybean oil has been well documented in its role in brain development, anti-inflammatory, and antioxidative activities particularly in Alzheimer’s models [ 116 , 117 ].…”
Section: Therapeutic Strategies For Chemotherapy-induced Inflammatmentioning
confidence: 99%
“…We suggested that dyslipidemia influences the cerebral blood perfusion through vascular disease, further leads to decreasing of cerebral oxygen level. Previous studies have reported that, dyslipidemia was a key factor of metabolic syndrome, and increases the risk of AD ( Gentile et al, 2020 ). Wingo et al (2019) found that elevated LDL levels were associated with higher probability of having early-onset AD, this novel findings highlight the important role of LDL in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, later reviews indicate the possibility that improving microbiota can be beneficial for ALS patients. Thus, studies that analyze the impact of microbiota transplantation to improve neurological disorders, [ 72 ] or the importance of diet factors in neurodegeneration [ 73 ] are outlined. It is especially in relation to the latter and once the main bacteria associated with ALS have been identified, we believe that it would be interesting to analyze the impact that antioxidants in the diet could have.…”
Section: Gut Microbiota and Alsmentioning
confidence: 99%